Do differences in gender and sport affect home advantage? A case study of the Commonwealth Games - Ramchandani, G.; Wilson, D. (International Journal of Performance Analysis in Sport, 2011)
This paper investigates differences in home advantage experienced in different types of events and sports contested in the Commonwealth Games. Alternative definitions of performance are employed to examine host nations' performances at home relative to proximate away editions immediately before and after hosting the competition. Depending on which performance indicator is used, it could be argued that host nations perform better at home more consistently in 'men only' events or in 'men only' and 'women only' events. By contrast, the analysis illustrates that home advantage is least likely to occur in 'mixed/open' events across all indicators examined. The sport specific analysis supports the view that home advantage is more prevalent in certain types of sports, particularly those which are held at the discretion of the host nation; in single competition sports; and, in sports involving more subjective input by officials. Assuming that achieving better performance is one, even if only minor, objective for nations hosting the competition, relevant national sports authorities should be conscious of which types of events and sports are likely to yield greater home advantage, so that they can determine the appropriate composition of their home sports programmes to complement their traditional strengths.